Analysis of economic structural change and its impact on community welfare in Bali province - Negara, I Gusti Ngurah Made Nata; Budhi, Made Kembar Sri; Saskara, Ida Ayu Nyoman; Tisnawati, Ni Made (Edelweiss Applied Science and Technology, 2025)
This study examines the economic structural changes and their impact on community welfare in Bali Province from 2017 to 2022. Structural change is assessed through sectoral contributions to GRDP, focusing on agriculture, tourism, and industry, and linked to welfare indicators such as the Gini ratio, poverty rate, wages, and employment absorption. This study employs the Adjusted Mazziotta Pareto Index (AMPI) as the analytical tool. Results show a significant shift in Bali’s economic structure, with tourism becoming increasingly dominant and agriculture’s share declining. This shift contributes to spatial welfare disparities, as only Denpasar City consistently falls into the high-welfare category, while most regencies remain in the low-welfare category. Persistent inequality and poverty hinder the improvement of equitable welfare. The study emphasizes the importance of economic diversification, revitalizing agriculture and local industries, and enhancing human capital development. Policy recommendations include reducing interregional disparities through balanced investment, developing the creative economy, and enhancing the empowerment of rural communities. Academically, this research advances the application of AMPI in regional development studies, while practically offering guidance for inclusive and sustainable economic policy in Bali.